PENGEMBANGAN MODIFIKASI BOLA PLASTIK TERHADAP PENINGKATAN KETERAMPILAN PASSING ATAS BOLA VOLI PADA SISWA KELAS VIII E SMP NEGERI 13 SURABAYA - PURBOJO, SUTO (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract To improve the quality of teaching physical education, sport and health, required an alternative to the use of methods, strategies, and media relevant learning and flexible learning materials. Special to the material passing the volleyball learning, many students at Junior High School 13 Surabaya encounter in doing so. It required a modification of instructional media such as the use of spherical modifications to improve it. In this study, the authors wanted to answer the problem: